2022
DOI: 10.1175/bams-d-21-0204.1
|View full text |Cite
|
Sign up to set email alerts
|

Tornado Radar Images and Path Directions: An Assessment of Public Knowledge in the Southeastern United States

Abstract: Due to the current use and reliance on tornado warning polygons, several published articles have concentrated on themes related to risk perception and interpretation of risk within and outside of polygons. Despite the general success of warning polygons, not everybody is able to spatially estimate their risk by looking at maps with tornado warning polygons. Using polygons in conjunction with radar images can improve comprehension and better inform protective action decision-making for tornado warnings. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…The study had considerable variation in self-reported distances, which can be explained by past exposure or direct tornado experience. Senkbeil et al (2022) examined how participants rely on tornado warning polygons and the extent how well they understand the polygons. The study recruited 1,023 participants using the Qualtrics panel.…”
Section: Tornado Experimental Studiesmentioning
confidence: 99%
“…The study had considerable variation in self-reported distances, which can be explained by past exposure or direct tornado experience. Senkbeil et al (2022) examined how participants rely on tornado warning polygons and the extent how well they understand the polygons. The study recruited 1,023 participants using the Qualtrics panel.…”
Section: Tornado Experimental Studiesmentioning
confidence: 99%